Multicomponent phase diagrams : applications for commercial aluminum alloys - Belov, N. A. (Elsevier, 2005)
Despite decades of extensive research and application, commercial aluminum alloys are still poorly understood in terms of the phase composition and phase transformations occurring during solidification, cooling, and heating. Multicomponent Phase Diagrams: Applications for Commercial Aluminum Alloys aims to apply multi-component phase diagrams to commercial aluminum alloys, and give a comprehensive coverage of available and assessed phase diagrams for aluminum-based alloy systems of different dimensionality. Features data on non-equilibrium phase diagrams, which can rarely be obtained from other publications. Extensive coverage of all groups of commercially important alloys and materials.